EFEKTIVITAS PUNGUTAN PAJAK REKLAME TERHADAPTINGKAT KEMANDIRIAN KEUANGAN DAERAH KABUPATEN BATANG HARI TAHUN 2010-2014 - Basuki Basuki (Jurnal Dinamika Manajemen, 2016)
The study aims to determine the development district Batang Hari advertisement tax years 2010-2014, the effectiveness of the advertisement tax levy Batang Hari district in 2010-2014, and the level of financial independence Batang Hari district in 2010-2014. The method used in this research is qualitaanalysis method, data collected by structured interview to dipenda Batang Hari district and regional development planning agency and county Batang Hari. Development of data analysis techniques using the advertisement tax ratio indicatordevelopment, the effectiveness of advertisement taxation using effectiveness ratio while the level of local financial independence using indicators of independence ratio.These result indicate that the development of the advertisement tax Batang Hari district of 10,14 % annually, the effectiveness of advertisement taxation has a verry effectifve influence on the level of local financial independence by 133,39%, and the level of local financial independence is still low with an average percentage rate of 5,36 % per year, this study shows that the effectiveness of advertisement taxation can increase the level of financial independence of local government areas in the district particularly Batang Hari.